If it's not what You are looking for type in the equation solver your own equation and let us solve it.
11x(-5)=(-90)
We move all terms to the left:
11x(-5)-((-90))=0
We add all the numbers together, and all the variables
11x(-5)+90=0
We multiply parentheses
-55x+90=0
We move all terms containing x to the left, all other terms to the right
-55x=-90
x=-90/-55
x=1+7/11
| X*(30+x)=7000 | | 6-0.5y=5-0.25y | | x+25²=100 | | 8x-2-x-4x=-3x+16 | | 5l+9=7l-23 | | 11x-(-5)=95 | | x^2-7x=x-13 | | 5x-2(4x+3=9 | | 23=4/6x | | -1/3=h/4-10/3 | | x^-7x=x-13 | | 9-x+5-3x=-1 | | 2n+3n+7=-21 | | 4(4x+5)=21x+18-5x+2 | | 10-2x=3.8x-16+3.8x | | -12/3w=-5 | | d+12=20 | | 7=3(x+0)-7 | | 4p+2p=6 | | 0.08x-2000/(x^2)-0.01=0 | | 374=2(10w)+2w | | 16=2(x+4)+8 | | 52=p-(3) | | 11y-8=9y+4 | | -13(4d-11)=18-5d | | 11y-8=9+4 | | 3h=7(0.2-0.42h)-10 | | 1k+10=-4-10 | | 5.4g+5=1.4g+17 | | 6.7g+10=2.7g+30 | | 81=3x=15 | | -2v+7(7v-5)=153 |